Regulations drive circular bioeconomy in emerging economies, but further action is required - Sathiskumar, Abinaya; Taron, Avinandan; Drechsel, Pay; Gebrezgabher, Solomie A. (International Water Management Institute, 2024)
Reducing greenhouse gas emissions from organic waste is a key pillar in advancing the circular bioeconomy. In the Global South, efforts have primarily focused on waste management regulations, with varying enforcement in these countries. These have focused mainly on human and environmental health without considering waste as a resource. For a genuine shift towards a circular bioeconomy, regulations must evolve to ensure environmental safety, promote resource recovery, and foster private sector engagement. This can be achieved through targeted policies, subsidies, financial incentives, and the development of public-private partnerships that open new market opportunities. Countries like Singapore, Brazil, China, Japan, South Korea, Ghana, and South Africa are leading the way with forward-thinking regulatory frameworks. These nations have built robust ecosystems by empowering statutory agencies to oversee waste management, engaging the private sector, and implementing financial mechanisms to support reuse and recovery. These innovative models are setting a precedent for successful circular bioeconomy implementation. Policymakers should take note of these approaches to craft impactful strategies that drive sustainable economic growth while addressing environmental challenges.